Cohesiveness from the Perspective of Social Exchange Theory and Group Communication - Rahma, Amanda Raissa; Octavianti, Meria (Communication, 2026)
Cohesiveness is a key aspect of group communication, as it reflects the degree of attachment members feel toward their group and how relationships can be maintained over time. However, existing studies on cohesiveness are predominantly examined from psychological perspectives, while communication as a process of social exchange has received less attention. This article aims to examine group cohesiveness using Social Exchange Theory, by placing communication as the main mechanism in social exchange. The method used in this study is a literature review of previous studies related to Social Exchange Theory, group communication, and cohesiveness. The findings indicate that cohesiveness develops through communication processes that facilitate interaction and social exchange, where group members evaluate their relationships based on perceived benefits and costs. Therefore, group cohesiveness can be understood as a relational outcome that emerges from ongoing communication within the group.